Atuação da coordenação pedagógica junto as professoras alfabetizadoras de escolas municipais de Uberlândia/MG: contribuições, desafios e possibilidades - Paula, Daniela Silva de (2021)
This research work has as its central theme the performance of pedagogical coordination with literacy teachers in municipal schools in Uberlândia. Assuming that the mediation of pedagogical coordination interferes in the teachers’ praxis, we elaborated the problematization: How is the performance of pedagogical coordination with literacy teachers in the 1st and 2nd year of Elementary School? Do the actions of pedagogical coordination support the work of teachers in their role of teaching children in the 1st and 2nd years of Elementary School to read and write? How? What challenges emerge from the interaction between pedagogical coordination and literacy teachers that reverberate in the teaching and learning process? From the problematizing questions, the objectives consisted of analyzing: the performance of pedagogical coordination for the pedagogical praxis of literacy teachers of the 1st and 2nd years of Elementary School; the challenges that emerge from the interaction between pedagogical coordination and literacy teachers and that reverberate in the teaching and learning process. Methodologically, the work is based on the principles of qualitative research, of the case study type. The Focus Group (FG) with the pedagogical coordinators and the Semi-structured Interview (SSI) with the teachers were used as research instruments. Through the organization of the data, the categories of analysis were defined as follows: 1 – Formative and professional constitution of pedagogical coordination: knowledge and identity; 2 – Pedagogical coordinators and literacy teachers: “being together”; within this category, we identified a subcategory defined as: 2.1 “literacy: weaving dialogues and building knowledge”; 3 – Challenges and contradictions in the work of pedagogical coordinators. The analysis shows that coordinators and teachers occupy central points in the teaching and learning process, especially in the literacy period. Therefore, there is a need for a collective search that breaks with school practices that do not respect the literacy student as a protagonist and builder of knowledge, aiming at an education committed to the ethical, aesthetic, social and emotional formation of all; in addition, considering the individuality of each one in this process.